Hypericum perforatum L. subsp. perforatum induces inhibition of free radicals and enhanced phototoxicity in human melanoma cells under ultraviolet light - Menichini, G. (Cell Prolif, 2013)
OBJECTIVES: Our interest continues in discovering phytocomplexes from medicinal plants with phototoxic activity against human melanoma cells; thus the aim of the present study was to assess antioxidant, anti‐inflammatory and phototoxic activity of Hypericum perforatum L. subsp. perforatum, and relate these properties to the plant's chemical composition. MATERIALS AND METHODS: Components of H. perforatum subsp. perforatum were extracted by hydroalcoholic solution and chemical profiles of preparations (HyTE‐3) performed by HPTLC. Linoleic acid peroxidation and DPPH tests were used to assess antioxidant activity, while MTT assay allowed evaluation of anti‐proliferative activity with respect to A375 human melanoma cells after irradiation with UVA dose, 1.8 J/cm(2). Inhibition of nitric oxide production of macrophages was also investigated. RESULTS: HyTE‐3 indicated better antioxidant activity with β‐carotene bleaching test in comparison to DPPH assay (IC (50) = 0.89 μg/ml); significant phototoxicity in A375 cells at 78 μg/ml concentration resulted in cell destruction of 50%. HyTE‐3 caused significant dose‐related inhibition of nitric oxide production in murine monocytic macrophage cell line RAW 264.7 with IC (50) value of 342 μg/ml. CONCLUSIONS: The H. perforatum subsp. perforatum‐derived product was able to suppress proliferation of human malignant melanoma A375 cells; extract together with UVA irradiation enhanced phototoxicity. This biological activity of antioxidant effects was combined with inhibition of nitric oxide production.